2018
DOI: 10.1007/s00520-018-4239-5
|View full text |Cite
|
Sign up to set email alerts
|

Patterns, perceptions, and perceived barriers to physical activity in adult cancer survivors

Abstract: Patient perceptions of PA benefits are strongly associated with improving PA levels after a cancer diagnosis. Clinician counseling should focus on patient education and changing patient perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 47 publications
5
54
1
Order By: Relevance
“…In our study, a pathological score of FACFT-Fas an indicator of fatigue-turned out to be the strongest negative predictor of motivation for PA. This important result is in line with several studies investigating barriers to PA in ACP [25,26] and cancer survivors [19,21,23]. These authors described fatigue as a main barrier of PA.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our study, a pathological score of FACFT-Fas an indicator of fatigue-turned out to be the strongest negative predictor of motivation for PA. This important result is in line with several studies investigating barriers to PA in ACP [25,26] and cancer survivors [19,21,23]. These authors described fatigue as a main barrier of PA.…”
Section: Discussionsupporting
confidence: 87%
“…These results were in concordance with several studies. Eng et al [23] examined PA behavior, perceptions and perceived barriers to PA in a study cohort of 1003 cancer survivors. In this study, patients with a sedentary lifestyle before diagnosis rarely improved their activity level after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each health behavior, patients were asked to rate the perceived impact of each behavior on three survivorship outcomes: quality of life, 5-year overall survival, and fatigue after a cancer diagnosis using a 7-point Likert scale (1 = "make much worse", 4 = "no effect", to 7 = "make much better"). [18][19][20][21]…”
Section: Assessment Of Outcomesmentioning
confidence: 99%
“…However, differences in both health behaviors and perceptions of these behaviors between immigrant and native‐born cancer survivors have not been explored. Previously, our group demonstrated that patient perceptions can be associated with health behavior changes after a cancer diagnosis …”
Section: Introductionmentioning
confidence: 99%